The Influence of Job Stress on Counterproductive Work Behavior with Neuroticism Personality as a Moderator Variable in State Civil Apparatus in Pekanbaru - Rahmadhani, Ifi Anjely; Cucuani, Hijriyati (Merpsy Journal, 2024)
The suboptimal performance of employees results in more cases of CWB. In many studies, CWB is often associated with work stress. Personality was also tested as a determining factor in the relationship between the two. In the big five personalities, neurotic personality are relatively consistent in strengthening the influence of work stress on work CWB compared to the other four personality types. This study aims to determine whether work stress influences CWB and whether neuroticism can moderate work stress on CWB on the State Civil Apparatus in Pekanbaru. The sampling technique uses quota sampling with a sample size of 147 employees who have worked for at least one year. The data will be collected by using Spector's Counterproductive Work Behavior checklist, IPIP-BFM-50 and the work stress scale. Data were analyzed using the Process by Andrew F. Hayes v4 for the SPSS tool. The results show that work stress affects CWB and neuroticism cannot moderate the effect of work stress on CWB. This research is expected to contribute to scientific knowledge and assist management in preventing and minimizing counterproductive work behavior, especially in establishing a conducive work situation and determining the proper employee criteria for recruitment.